Impact of Demonetization on Shareholders’ Wealth: Case of India - Abhishek , Parikh (Asian Journal of Empirical Research, 2019)
This paper examines the impact of demonetization on shareholders’ return in India. After the demonetization announcement in India (8 November 2016) money became a significant source of stress. It is documented that this announcement had various effects on individual, social, and economic levels. The data of shareholders’ returns from before and after demonetization for 60 months from October 2012 to November 2017 were collected using a capital line database. The results depict that demonetization ruined shareholders’ wealth for 12 months. However, in the long run it gives investors very attractive returns.